Data Journalism in the Spanish Caribbean Digital Media - Ramaris Albert Trinidad (Anàlisi: Quaderns de Comunicació i Cultura, 2020)
21st-century journalism is characterized by new trends that facilitate the production of digital and novel contents. Among them, most notable is data-driven journalism, which collects structured information and analyzes it in-depth to present it in more versatile formats through interactive visualizations and other multimedia tools. This specialty serves to tell stories based on vast amounts of information that, without the assistance of a computer and the application of statistical methods, would be challenging to report. This work is a pilot study about the degree of penetration of data journalism through a comparative study of the journalistic media of the Spanish-speaking Caribbean. For this purpose, an exploratory pilot questionnaire investigated the processes and techniques used by journalists in the preparation of publications in digital media of Puerto Rico, Cuba, and the Dominican Republic, in order to determine whether they apply data journalism from the defining elements that Paul Bradshaw establishes in his inverted pyramid of data journalism. The findings pointed out that journalists from these countries vary in the level of frequency of use of the five characteristic functions, of which the analysis of databases is the most used by all. The respondents agree that the least used data journalism techniques are the collection of data through contests or open collaboration projects (crowdsourcing) and the development of tools and informative web applications based on database contents. The digital journalists who have trained in this discipline did so, mainly, through workshops and practical seminars they took on their own initiative.